Қазақ тілі мен əдебиеті сабағында жаңа технологияны ұтымды пайдалану арқылы ұлттық құндылықтарды оқушы бойына дарыту - Байжуманова, А. Ж. (My University, 2016)
In this article, the authortonehes upon the problems of modern education discksses the initiatives in educational sphene and shares with her teaching experience. The author emphasis on the need ofinstiling the national values into young generation throngw extensive knowledge using modern of new technology.
Keywords: new technologies in the field of education; group work; action research; national values; national education; constructive training; practices